Abusive customer behaviour and frontline employee turnover intentions in the banking industry: The mediating role of employee satisfaction - Bylon ABeeku Bamfo; Courage Simon Kofi Dogbe; Harry Mingle (Cogent Business & Management, 2018)
Purpose—The study aims to examine the mediating role of frontline employee job satisfaction in the relationship between abusive customer behaviour and employee turnover intentions in the banking industry.Design/Methodology/Approach—The study sampled 186 frontline employees from 10 banks in the Ashanti Region of Ghana. The data analysis software used was STATA. The main method of data analysis was structural equation modelling; however, a confirmatory factor analysis was first conducted to check for the validity and reliability of the research instrument. A mediation analysis was finally conducted and confirmed using Sobel test.Findings—The study revealed that abusive customer behaviour has a negative and significant effect on frontline employee satisfaction in the banking sector. Frontline employee satisfaction also has a negative and significant effect on employee turnover intention in the banking industry. Abusive customer behaviour has a positive and significant effect on frontline employee turnover intentions in the banking sector. Frontline employee satisfaction also has a partial mediating effect on the relationship between abusive customer behaviour and employee turnover intentions in the banking industry.Originality/Value—In the banking industry, frontline employees such as tellers play a critical role as they serve as intermediaries between the banks and the public. However, empirical studies on the influence of customer behaviour on employees have largely concentrated on other sectors. Although literature supports the individual relationships among the variables studied, there existed a gap on the mediating role of employee satisfaction, especially in the banking sector.
Keywords: 650